Vitamin A, C, E and risk of breast cancer according to menopausal status in Malaysia - Mohd Razif, Shahril; Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Suhaina, Sulaiman (2016)
Vitamin A, C and E intake has been shown to play a role in the etiology of breast cancer, but the findings have been inconsistent and limited to developed countries with higher cancer incidence. Therefore, the aim of this study is to examine the association of premenopausal and postmenopausal breast cancer risk with vitamin A, C and E intake from dietary sources. This is a population based case-control study conducted in Malaysian population among 382 breast cancer patients and 382 control group. Dietary intake was assessed via an interviewer-administered food frequency questionnaire. Logistic regression was used to compute odds ratios (OR) with 95% confidence intervals (CI) and a broad range of potential confounders were included in analysis. The results of this study shows a significant decreased risk of breast cancer among premenopausal (ORQ4 to Q1=0.38, 95% CI, 0.12 – 0.55, p-trend=0.001) and postmenopausal (ORQ4 to Q1=0.26, 95% CI, 0.03 – 0.75, p-trend=0.017) women was observed in the highest quartile of beta-carotene intake. Meanwhile, a higher intake of vitamin C showed significantly lowered risk only for premenopausal women (ORQ4 to Q1=0.13, 95% CI, 0.03 – 0.32, p-trend=0.001). As a conclusion, beta-carotene intake was independently related to pre- and postmenopausal breast cancer risk, while vitamin C intake was associated with decreased risk among premenopausal women only. However, no association was observed for vitamin A especially retinol and vitamin E intake from dietary sources.